Medical Management of Acute Spinal Cord Injury with Aspiration pneumonia in a Kid - P K, Ramkumar; M, Saravanan; K, Vijayakaran; S L, Sundaram (Indian Journal of Veterinary Medicine, 2024)
A two-month-old, non-descript female goat kid was brought to the Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu, with a history of continuous high-pitched bleating, respiratory distress, and forelimb paresis over the past two days. The animal has appeared lethargic with an abnormal gait. Neurological examination revealed sluggish sensory and motor reflexes in the forelimbs and palpation elicited pain in the thoracic and dorsal spinal areas (C7-T2). Auscultation revealed exaggerated heart sounds and prolonged expiration. Radiographic examination ruled out spinal involvement but revealed left lung consolidation with pulmonary infiltration. Cerebrospinal fluid analysis showed an increase in neuron-specific enolase (NSE). The condition was tentatively diagnosed as acute spinal cord injury with aspiration pneumonia. Inj. Progesterone and intranasal Budesonide were administered along with a Progesterone patch applied to the lateral neck region. Successful medical management led to gradual clinical improvement observed from the seventh day and completely recovered after 15 days of treatment.